2014
DOI: 10.1175/jpo-d-13-0217.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Variability of Antarctic Circumpolar Current Fronts Inferred from 1992–2011 Altimetry*

Abstract: Antarctic Circumpolar Current (ACC) fronts, defined as water mass boundaries, have been known to respond to large-scale atmospheric variabilities, especially the Southern Hemisphere annular mode (SAM) and El Niño–Southern Oscillation (ENSO). Distinct patterns of localized variability in meridional front displacements during 1992–2011 are derived from the analysis of satellite sea surface height data. Major basin-scale differences are found between the southeast Pacific (150°–90°W) and the southeast Indian (75°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
186
4
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(214 citation statements)
references
References 71 publications
15
186
4
4
Order By: Relevance
“…The most significant of these fronts, responsible for the majority of the ACC volume transport (e.g., Cunningham et al, 2003), are the Subantarctic Front (SAF) and the polar front (PF). However, even this is not a realistic picture of the circulation in the Southern Ocean, since at any specific time, there can be from 3to 10 narrow jets around the fronts that are highly variable in strength and location, masking the specific frontal boundary Rintoul, 2007, 2009a, b;Sallee et al, 2008;Thompson et al, 2010;Thompson and Richards, 2011;Langlais et al, 2011;Graham et al, 2012;Chapman, 2014;Gille, 2014;Kim and Orsi, 2014;Shao et al, 2015;Chapman, 2017a). Although positions of fronts have been estimated throughout the Southern Ocean, primarily using gradients of subsurface density measured from hydrographic sections (Orsi et al, 1995), contours of dynamic topography Rintoul 2007, 2009a, b;Langlais et al, 2011), or a combination of both (Kim and Orsi, 2014), in many places there are no strong currents that can be measured near the front position (Chapman, 2014(Chapman, , 2017a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant of these fronts, responsible for the majority of the ACC volume transport (e.g., Cunningham et al, 2003), are the Subantarctic Front (SAF) and the polar front (PF). However, even this is not a realistic picture of the circulation in the Southern Ocean, since at any specific time, there can be from 3to 10 narrow jets around the fronts that are highly variable in strength and location, masking the specific frontal boundary Rintoul, 2007, 2009a, b;Sallee et al, 2008;Thompson et al, 2010;Thompson and Richards, 2011;Langlais et al, 2011;Graham et al, 2012;Chapman, 2014;Gille, 2014;Kim and Orsi, 2014;Shao et al, 2015;Chapman, 2017a). Although positions of fronts have been estimated throughout the Southern Ocean, primarily using gradients of subsurface density measured from hydrographic sections (Orsi et al, 1995), contours of dynamic topography Rintoul 2007, 2009a, b;Langlais et al, 2011), or a combination of both (Kim and Orsi, 2014), in many places there are no strong currents that can be measured near the front position (Chapman, 2014(Chapman, , 2017a.…”
Section: Introductionmentioning
confidence: 99%
“…Using the contour method and tracking how the dynamic topography contours associated with a front position shift in time, Sokolov and Rintoul (2009b) found that the SAF and PF had both moved south by approximately 60 km over 15 years between 1993 and 2008. Kim and Orsi (2014) recently updated this analysis and found that while the average frontal position across the Southern Ocean indicates a strong southward shift, this is due primarily to substantial shifts only in the Indian Ocean sector. They found no significant shifts throughout the Pacific or Atlantic Ocean sectors using the contour method.…”
Section: Introductionmentioning
confidence: 99%
“…남극해는 세계에서 표층 영양염이 가장 풍부한 해역으로, 남극 바람장이 일으키는 대규모 연 안 용승이 심해의 풍부한 영양염을 식물플랑크톤이 위치 한 표층까지 공급하기 때문이다 (Hopkinson et al 2007). (Sallée et al 2008;Kim and Orsi 2014 (Lovenduski and Gruber 2005;Park et al 2010;Sallée et al 2010;Carranza and Gille 2015).…”
Section: 서 론unclassified
“…바람장 변화 이외에 남극 해양 환경에 주요한 변화를 유발하는 대기 경년변동성 중 하나는 적도 남태평양의 해 양/대기 변화를 나타내는 엔소(El Niño Southern Oscillation, ENSO)이다 (White and Peterson 1996;Yuan 2004;Verdy et al 2006;Sallée et al 2008;Stammerjohn et al 2008;Vivier et al 2010;Ding et al 2011;Kim and Orsi 2014). 적도 태평양 표층해수가 평년에 비하여 따뜻해지는 엘리 뇨 시기에 적도에서 시작된 로스비 파열(Rossby wave train)의 일부로 고기압 어노말리가 남태평양 상에 생성된 다 (Turner 2004;Fogt et al 2011).…”
Section: 서 론unclassified
See 1 more Smart Citation